2021
DOI: 10.1074/jbc.ra120.015389
|View full text |Cite
|
Sign up to set email alerts
|

An endogenous PI3K interactome promoting astrocyte-mediated neuroprotection identifies a novel association with RNA-binding protein ZC3H14

Abstract: Astrocytes can support neuronal survival through a range of secreted signals that protect against neurotoxicity, oxidative stress, and apoptotic cascades. Thus, analyzing the effects of the astrocyte secretome may provide valuable insight into these neuroprotective mechanisms. Previously, we characterized a potent neuroprotective activity mediated by retinal astrocyte conditioned media (ACM) on retinal and cortical neurons in metabolic stress models. However, the molecular mechanism underlying this complex act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 99 publications
(162 reference statements)
0
6
0
Order By: Relevance
“…We previously reported that in addition to their known pro‐resolution functions, lipoxins demonstrate an exciting novel protective bioactivity directly on neurons [14] . In particular, LXB 4 was surprisingly 20‐fold more potent than LXA 4 in an established neuronal injury model, [14,39] and also active in a variety of primary neurons, including cortical and hippocampal cells, and retinal ganglion cells. These broad neuroprotective effects were subsequently correlated with demonstrated LXB 4 efficacy in vivo using both acute and chronic models of retinal ganglion cell death associated with the common neurodegenerative disease glaucoma, a leading cause of vision loss and blindness worldwide [40–42] .…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported that in addition to their known pro‐resolution functions, lipoxins demonstrate an exciting novel protective bioactivity directly on neurons [14] . In particular, LXB 4 was surprisingly 20‐fold more potent than LXA 4 in an established neuronal injury model, [14,39] and also active in a variety of primary neurons, including cortical and hippocampal cells, and retinal ganglion cells. These broad neuroprotective effects were subsequently correlated with demonstrated LXB 4 efficacy in vivo using both acute and chronic models of retinal ganglion cell death associated with the common neurodegenerative disease glaucoma, a leading cause of vision loss and blindness worldwide [40–42] .…”
Section: Resultsmentioning
confidence: 99%
“…For western blot analysis, cell and tissue protein was collected in RIPA lysis buffer containing protease and phosphatase inhibitors, homogenized, and run on a 12% sodium dodecyl sulfate polyacrylamide gel according to standard practices. The protein was then transferred onto a polyvinylidene difluoride membrane and blocked with 5% bovine serum albumin as previously described (Alqawlaq et al, 2020). Membranes were incubated with primary antibodies raised against ANXA4 (1:2000 dilution; Sigma) and glyceraldehyde 3‐phosphate dehydrogenase (1:10,000 dilution; Calbiochem).…”
Section: Methodsmentioning
confidence: 99%
“…Yet, the cellular injury and mechanosensing mechanisms linking this strain to cellular damage are critically unclear, and remain a key research question. The resulting chronic strain injury induces a cascade of pathological effects that prominently include cytoskeletal remodeling and para‐inflammatory activation of ONH astrocytes (Almasieh et al, 2012; Alqawlaq et al, 2019, 2020; Livne‐Bar et al, 2016), which are crucial for providing structural and homeostatic support to retinal ganglion cell (RGC) axons as they exit the eye to form the optic nerve (Alqawlaq et al, 2020; Guo et al, 2018; Livne‐Bar et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] We and others have uncovered increasing evidence that astrocytes can also play essential roles in maintaining and promoting neuronal homeostasis. [11][12][13][14][15][16] A recent study by our groups indicated that the levels of astrocyte-derived lipoxins A 4 (LXA 4 ) and B 4 (LXB 4 ) in the retina and optic nerve decreased following acute excitotoxic injury. 17 Lipoxins are members of the specialized pro-resolving mediator (SPM) family of polyunsaturated fatty acid metabolites, derived from arachidonic acid.…”
Section: Introductionmentioning
confidence: 99%
“…710 We and others have uncovered increasing evidence that astrocytes can also play essential roles in maintaining and promoting neuronal homeostasis. 1116…”
Section: Introductionmentioning
confidence: 99%